(untitled) (Journal of the College of Basic Education, 2026)
This research deals with the hadith terminology that is unique to Al-Majlisi, as he used some hadith terms that are not commonly used by hadith scholars. I tried during this research to investigate these terms, and to graduate a group of hadiths that he described with these terms, and to explain the reason for using these descriptions on them, and I explained the status of their narrators. Among those descriptions are: “Weak according to the well-known, but authentic in my opinion,” “Weak like a trustworthy narrator,” “Weak according to the well-known, but considered in my opinion,” “Weak according to the well-known, but perhaps trustworthy,” “Unknown according to the well-known, but perhaps considered good,” and “Disputed about, but authentic in my opinion.”